(untitled) (Scientia Agricola, 2018)
Cachaça poses many quality (appearance, taste, consumer acceptability) and safety hazards (chemical, metal, and microbiological contaminations during the process). In this work, an effort is made for the quality and safety analysis of cachaça, by describing and outlining the potential hazards in every step of the process. This study revealed that the critical control points (CCPs) involved in Good Manufacturing Practices (GMP) to prevent cachaça safety hazards are the stages of sugarcane growing, sugarcane harvesting, fermentation, distillation, and aging process. The most significant factors for both CCPs and critical points (CPs) that should be controlled are determined. The implementation of the Hazard Analysis and Critical Control Point (HACCP) system in small distilleries of cachaça has been very helpful to provide the required safety for domestic consumers and boost cachaça exportations. Therefore, the main objective of the cachaça industry is to achieve production consistency.